Influencia del taller "LIKE WRITING" en el desarrollo de la habilidad de escritura (Writing) del idioma inglés en los estudiantes de la asigna tura de problemas específicos de la gramática inglesa I del IV ciclo de la Facultad de Educación y Humanidades de la Escuela Académico Profesional de Idiomas de la Universidad Nacional de San Martin, Tarapoto- 2011-II - Lujan Romero, Esgar Jhonny (2011)
The present research is born from the need to be able to develop the skill of the writing in the English language and contains a new methodological and innovative offer based on the constructivist approach, across the workshop I LIKE WRITING what is looked is to promote through its stages (Motivating, Knowing Vocabulary, Practicing and Producing) the development of this skill in the students of the subject of Specific Problems of the English Grammar I of the cycle IV, faculty of education and humanities of the Academic Professional School of Languages of the National University of San Martin-Tarapoto - 2011-II. Our proposal is based mainly on the development of written texts through a series of strategies involved in the four stages in this way, and with a comfortable environment, the student is able to write much more than before and much better, as the workshop is also designed to enable the student to realize their common mistakes and correct uses within a grammatical structure, so the student feels free will be able to produce written texts with a superlative degree of confidence , which is demonstrated in the results obtained after the application of our research. Finally we dare to assert the effectiveness of the workshop I LIKE WRITING, a claim corroborated by tabulations of data obtained after the application of this workshop which showed a more than encouraging results we showed that I LIKE WRITING workshop if significantly influenced in developing the skill of writing the English language to students of the subject of specific problems of English Grammar I of the 4th cycle, faculty of education and humanities of the Academic Professional School of Languages of the National University of San Martin-Tarapoto- 2011-II